Bureaucratic Challenges in Village Fund Management: Effects on Tourism Village Community Welfare - Sumada, I Made; Aryana, I Wayan Putu Sucana; Kartika, I Made; Suwandana, I Made Adi; Adnyana, Yudistira (Ilomata International Journal of Management, 2025)
This study describes the bureaucratic challenges in managing village funds and their impact on welfare improvement in the tourism village community by taking Badung Regency in Bali as the case study. Specifically, it examines how government role, governance, and social capital may influence fraud and economic performance in determining community welfare improvement. In this quantitative study, data were obtained from 150 respondents who used structured questionnaires with a Likert scale ranging from 1-5. Data was analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results indicated that governance and social capital significantly enhance economic performance and welfare at the community level and reduce fraud. Financial performance at the district/municipality level mediates the positive influence of governance and social capital on welfare at the community level. In contrast, fraud negatively mediates the impact of governance on economic performance. These findings emphasize the need to strengthen governance, build social capital, and minimize fraud to maximize village funds for sustainable community development in tourism villages. The study provides actionable insight into how policymakers and stakeholders can improve village fund management and enhance rural welfare.